Distribuição de lotes carregados de minério de ferro ferrovia-porto: uma abordagem por simulação a eventos discretos - Vieira, Rowena Maria Teixeira (2018)
Given the current scenario of uncertainty related to the price of iron ore, major mining companies have sought in their activities to operational excellence, maintaining its production scale, but with much lower costs. Therefore, it is necessary the supply chain review your current operations and, above all, their planning, among them the part related to rail transport. Thus, it was proposed to develop a model of simplified discrete simulation of a rail yard iron ore with destination route (Railroad-Port), with the objective of assisting in the distribution analysis of lots loaded with iron ore in tactical level. It was used the Arena software to implement the simulation model, which it was possible to evaluate the level of use of available resources (locomotives, car dumpers and routes) and the iron ore discharge capacity in a known railroad and port of Brazil. The developed model considered the historical data of the years 2015 and 2016 and was validated with a confidence interval of 95%. Scenarios for the circulation of larger trains (more economical) were evaluated, and the results showed that there was idle capacity, and thus capacity for a potential increase of annual volume discharged around 5%.